Adaptation and Deconstruction: Emma Rice’s (2022) Adaptation of Wuthering Heights - Mesut Günenç (Litera: Dil, Edebiyat ve Kültür Araştırmaları Dergisi)
This study seeks to analyse the adaptation of Emily Brontë’s canonical work focusing on Emma Rice’s play Wuthering Heights (2022) and its transformation of the conventional forms of Brontë’s canonical original into more experimental directions. Adaptation is “an acknowledged transposition of a recognisable other work or works” (Hutcheon, 2006, p. 8). Catherine Rees clarifies the distinctive appeal of adaptation whereby “another attraction of adaptation is the opportunity it offers for presenting texts in a new context” (Rees, 2017, p. 3). Within this context, Emma Rice’s play, analysing the original text in a new format, interprets Catherine and Heathcliff as Greek gods. The theatrical version of Wuthering Heights, performed at Bristol Old Vic in front of a live audience, retold a canonical story. Emily Brontë’s Wuthering Heights had a great impression on the Victorian community when it was first published. Through studies and the medium of adaptation, Brontë’s work has been analysed and discussed in the ages and reached more and more readers and audiences. This study delves into how an adaptation of Wuthering Heights in the form of performance is represented by Emma Rice. Through music, dance, grief, hope, passion and revenge, Rice portrays a contemporary revenge tragedy by adapting Emily Brontë’s magnum opus into a theatrical performance. By referring to the ancient chorus, Rice tries to represent Catherine and Heathcliff as a tragic heroine and a hero. In Rice’s adaptation, Heathcliff’s adoption is turned into an experimental performance.